Koncepcja i podstawy prawne dla nowego ujęcia rejestru – „Rejestr 3.0 - Szostek, Dariusz; Malarewicz-Jakubów, Agnieszka; Castellani, Maddalene (Białostockie studia prawnicze (Uniwersytet w Białymstoku), 2025)
This article introduces the authors’ original concept of ‘Register 3.0’, a modernized model of public registers designed to meet the demands of the evolving European digital economy and the increasing algorithmization of law. In the context of significant regulatory developments in the European Union, particularly the adoption of the eIDAS2 Regulation, the authors emphasize the urgent need to reformulate the architecture and function of public registers. Register 3.0 is envisioned as an interoperable, automated, and highly secure data system, built upon cutting-edge technologies. A central component of this concept is datafication, understood as the real-time and automatic acquisition of data from reference sources without the need for manual processing. The article presents a comparative analysis of three generations of registers: traditional data repositories (Register 1.0), interoperable systems with partial automation (Register 2.0), and advanced registers integrated with algorithmic legal frameworks (Register 3.0), capable of issuing legal decisions and initiating cascading legal consequences autonomously. The authors discuss the possibility of embedding legal rules within algorithmic architecture – a process referred to as ‘crypto-law’ – where traditional legal norms are encoded directly into secure digital environments, thus enabling fully automated legal and administrative processes. Furthermore, the article explores practical applications of this concept, such as the Unified Business Registry system in Dubai, as proof of the feasibility and effectiveness of Register 3.0 in real-world scenarios. By examining the legal, technological, and institutional prerequisites for implementation, the authors argue that Register 3.0 not only supports the automation of state functions and judicial systems but also serves as a foundation for next-generation legaltech solutions. The study opens the door to further interdisciplinary research on adapting European legal frameworks to accommodate these innovations, positioning Register 3.0 as a cornerstone of future digital governance.